2012
DOI: 10.1016/j.febslet.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical interactions between HIV‐1 integrase and reverse transcriptase

Abstract: a b s t r a c tHuman immunodeficiency virus (HIV) infection yields a high level of non-integrated viral DNA in the infected cells and up to 99% of total viral DNA can be capable of transcription. This capability of non-integrated viral DNA is reducing the efficacy of anti-HIV drug development approaches that solely focus on the integration reactions of viral replication. Using kinetic modeling, we show the transient coordinated regulation of viral DNA production by retrovirus-encoded interacting enzymes revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 37 Similarly, previous studies have reported that mutations of retroviral integrase affected reverse transcription. 38 , 39 , 40
Figure 4 Genome Integrations of Retroviral Vectors When Having Residual Primer-Binding Site Sequences (A) Schematic overview of retroviral genomic DNA processing during integration. Left panel: if RNA processing during reverse transcription is incomplete, residual primer-binding site sequences can form in the 3′ LTR end of the provirus (refer to Figure S2 ).
…”
Section: Resultsmentioning
confidence: 99%
“… 37 Similarly, previous studies have reported that mutations of retroviral integrase affected reverse transcription. 38 , 39 , 40
Figure 4 Genome Integrations of Retroviral Vectors When Having Residual Primer-Binding Site Sequences (A) Schematic overview of retroviral genomic DNA processing during integration. Left panel: if RNA processing during reverse transcription is incomplete, residual primer-binding site sequences can form in the 3′ LTR end of the provirus (refer to Figure S2 ).
…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 RT has been identified to physically interact with viral integrase by using GST pulldown assays, coimmunoprecipitation assays, dot blot assays, NMR spectroscopy analyses, and surface plasmon resonance analyses (101)(102)(103)(104)(105)(106)(107)(108). The binding of integrase to RT does not require multimeric integrase or an integrase with complete enzymatic activity (108).…”
Section: Rt-integrase Interactionmentioning
confidence: 99%
“…HIV integrase has been determined to physically interact with RT by using GST pulldown assays, coimmunoprecipitation assays, dot blot assays, NMR spectroscopy, and surface plasmon resonance analyses (101)(102)(103)(104)(105)(106)(107). Two functions of the integrase-RT interaction have been proposed.…”
Section: Integrase-rt Interactionmentioning
confidence: 99%
“…RT and IN proteins play central roles in the HIV-1 life cycle. The replication of HIV-1 upon successful penetration of the host cell requires the reverse transcription of viral RNA genome and the integration of newly synthesized pro-viral DNA into the host genome by RT and IN for reverse transcription of the RNA genome and integration, respectively ( Chakraborty et al. 2013 ).…”
Section: Introductionmentioning
confidence: 99%